2021
DOI: 10.1007/s10021-020-00599-0
|View full text |Cite
|
Sign up to set email alerts
|

Litter Decomposition Rates of Biocrust-Forming Lichens Are Similar to Those of Vascular Plants and Are Affected by Warming

Abstract: Despite the high relevance of communities dominated by lichens, mosses and cyanobacteria living on the soil surface (biocrusts) for ecosystem functioning in drylands worldwide, no study to date has investigated the decomposition of biocrust-forming lichen litter in situ. Thus, we do not know whether the drivers of its decomposition are similar to those for plant litter (e.g., importance of abiotic degradation through UV radiation), the magnitude of lichen decomposition rates and whether they will be affected b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…Thus, P from dead lichen tissues is likely transferred to the topsoil and incorporated to occluded and non‐occluded forms through biological and chemical transformations (García‐Velázquez et al, 2020). Strong evidence of rapid lichen litter decomposition increased by warming in the same area of our study has been recently found (Berdugo et al, 2021). Taken together, these results suggest that the microbial community could transfer mid‐term available P coming from lichen tissues to more labile ones through microbial P solubilization from occluded P contributing to the increase in P available for plants.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, P from dead lichen tissues is likely transferred to the topsoil and incorporated to occluded and non‐occluded forms through biological and chemical transformations (García‐Velázquez et al, 2020). Strong evidence of rapid lichen litter decomposition increased by warming in the same area of our study has been recently found (Berdugo et al, 2021). Taken together, these results suggest that the microbial community could transfer mid‐term available P coming from lichen tissues to more labile ones through microbial P solubilization from occluded P contributing to the increase in P available for plants.…”
Section: Discussionsupporting
confidence: 89%
“…Previous experiments conducted in drylands have reported that simulated warming has been found to reduce microbial diversity and biomass (DeAngelis et al, 2015;Delgado-Baquerizo et al, 2014;Maestre et al, 2015), the cover of biocrust-forming lichens (Ladrón de Guevara et al, 2018) and higher UV degradation of plant and lichen litter (Almagro et al, 2015;Belnap, 2011;Berdugo et al, 2021;Castenholz and Garcia-Pichel, 2012). The death of biocrust-forming lichens (including the release of immobilized P by the microbes) and the subsequent decomposition of their tissues mediated by warming (Berdugo et al, 2021;Ladrón de Guevara et al, 2018) may explain the increase in labile P and organic P in the topsoil in our experiment.…”
Section: Warming Affects Soil P Poolsmentioning
confidence: 98%
“…The role of photodegradation in litter decomposition is well established [ 84 , 112 ]. There is now more evidence that photodegradation plays a key role in moist and temperate systems, such as in temperate forests [ 117 ], as well as in dryland systems [ 118 , 119 ]. How much plant litter gets exposed to solar radiation, including the UV component, varies among ecosystems.…”
Section: Biogeochemical Cyclesmentioning
confidence: 99%
“…Endophytic fungi are generally latent saprotrophs or pathogens, but it remains unclear to what extent endolichenic fungi, other than lichenicolous taxa, actually have a latent presence within lichen thalli or whether they just represent spores or hyphae of widespread, weedy taxa accidentally trapped or otherwise associated with the latter. The role of fungi as saprotrophs on dead lichens remains unclear, although decomposition of lichen thalli has been widely studied (Guzman et al 1990;Greenfield 1993;Biazrov 1994;McCune and Daly 1994;Caldiz et al 2007;Campbell et al 2010;Asplund and Wardle 2012;Berdugo et al 2021). Given the diversity of mycoparasites in general and lichenicolous fungi attacking and damaging lichen mycobionts in particular, it seems feasible that certain fungi play a role in decomposing lichen thalli, although it has also Fig.…”
Section: What Are Lichens and How Should They Be Named?mentioning
confidence: 99%